Developing Tsunami-Resilient Communities The National Tsunami Hazard Mitigation Program - Bernard, E.N (Springer Netherlands : Imprint: Springer, 2005)
Tsunamis remain an ever-present threat to lives and property along the coasts of most of the world's oceans. Because of the geographical extent of U.S. coastlines, an earthquake in Alaska can generate a local tsunami for Alaskans and, hours later, a distant tsunami for communities in Hawaii and along the Pacific Coast . This volume chronicles the development and accomplishments of a joint State/Federal partnership that was forged to reduce tsunami hazards along U.S. coastlines - the National Tsunami Hazard Mitigation Program. By integrating hazard assessment, warning guidance, and mitigation activities, the program has created a roadmap and a set of tools to develop communities more resilient to local and distant tsunamis. Among the set of tools are tsunami forecasting, educational experiments, early alerting systems, and design guidance for tsunami-resilient communities. Part of this book has already been published in a recent journal issue.